If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + -6 = 77 Reorder the terms: -6 + A = 77 Solving -6 + A = 77 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + A = 77 + 6 Combine like terms: -6 + 6 = 0 0 + A = 77 + 6 A = 77 + 6 Combine like terms: 77 + 6 = 83 A = 83 Simplifying A = 83
| 12x^4+8x^2-20=0 | | 245=x+166 | | -k+5(-3k+3)=15-4K | | P^3-4p^2=O | | w+2=98 | | sen4x=1/2 | | 5+14a=9a-2 | | 15+14p=2 | | 3(-4)=9 | | j-47=29 | | 2x+1+2x=96 | | (8)/(3X^2) | | -3x^2+24x=17 | | 92=x+20 | | y+2.7=18.3 | | 120n=1320 | | 39-3x=7(x+2)-5 | | A-15x=0 | | y=-0.5*2 | | 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 |